Changed Profile of Serum Transferrin Isoforms in Primary Biliary Cholangitis - Agnieszka Grytczuk (Journal of Clinical Medicine, 2020)
Liver damage affects the synthesis of proteins and glycoproteins, and alters their posttranslational modification, such as glycosylation changing the serum profile of glycoprotein isoforms. The retention of hydrophobic bile acids in the course of cholestatic liver diseases is a major cause of liver damage in primary biliary cholangitis (PBC). The study objective was to determine the serum profile of transferrin isoforms in primary biliary cholangitis and compare it to transferrin isoforms profile in extrahepatic cholestasis. The study was carried out in 76 patients with PBC and 40 healthy blood donors. Transferrin isoforms were analyzed by the capillary electrophoresis method. The mean relative concentrations of disialotransferrin and trisialotransferrin in PBC were significantly lower than those in the healthy subjects (p < 0.001, p = 0.011; respectively). None of the transferrin isoforms changed according to the disease severity evaluated by the Ludwig scoring system. However, the disease stage affected the activity of alkaline phosphatase (ALP) and γ-glutamyl transferase (GGT), and albumin level (p = 0.002; p = 0.013 and p = 0.005, respectively). Our results indicate that serum profile of transferrin isoforms alters primary biliary cholangitis and differs in comparison to transferrin isoforms profile in extrahepatic cholestasis. The decreased concentrations of lower sialylated isoforms of transferrin (low percentage share in total transferrin level) are not associated with the histological stage of disease.